Binder characterization and performance of asphaltic concrete modified with waste cooking oil - Wan Azahar, Wan Nur Aifa (2018)
The use of waste cooking oil (WCO) in binder modification is widely explored in response to waste management issue. However, the decreasing rheological performance pattern trend at high temperature by using WCO is globally recorded and yet still unresolved. This poor performance is due to the high acidity of the WCO. To resolve this issue, a chemical treatment was proposed to reduce the acidity of the WCO. Therefore, the aim of this study was to evaluate the performance of binders modified with untreated and treated WCO. It was carried out in three phases. In Phase 1, the physical and rheological tests of binder (penetration, softening point, viscosity and DSR) were conducted to determine the optimum percentages of untreated and treated WCO (between 0, 5, 10, 15 and 20%) in modifying the binder. In Phase 2, the optimums WCOs were utilised for further mechanical performance evaluation of Asphaltic Concrete 14 (AC14) mixture through Marshall stability, resilient modulus, dynamic creep and indirect tensile strength (ITS). The morphology and microstructure observations were performed in Phase 3 to investigate the adhesion bonding between modified binder and aggregates. The test results showed that the acidity of the WCO decreased after chemical treatment. The rheological test showed that the failure temperature of binder modified using the treated WCO has increased to 70 oC. In addition, treated WCO mixture recorded superior performance by being less susceptible to permanent deformation as compared to the control mix. Besides, the microstructure analysis revealed that low surface roughness of binder modified with treated WCO has strengthened the adhesion bonding with aggregates. In conclusion, the chemical treatment had improved the treated WCO performance in the modified binder as asphalt paving materials.